Poważny brak rozeznania oceniającego (kan. 1095, n. 2 KPK) w wyroku Roty Rzymskiej c. Mckay z 14.10.2004 r. - Góralski, Wojciech (Ius Matrimoniale, 2014)
In the Lafayetten. case regarding a declaration of the marriage (which lasted 25 years) due to gravis defectus discretionis iudicii of both parties, the judgment declaring the marriage invalidity was issued in the first instance (the lack of discernment of the spouses was declared). After the appeal brought by the defendant (the woman) to the Roman Rota the case was examined (by tumus c. McKay) in the ordinary proceedings and resulted in the negative judgment, thus, the invalidity of the challenged marriage was not proved. The judgment of the Roman Rota is an example of a thorough evaluation of evidence, and the critical valuation of experts’ opinion in particular.